TRANSIENT RECEPTOR POTENTIAL ANKYRIN 1 (TRPA1) SEBAGAI TARGET TERAPI MUTAKHIR DALAM PENATALAKSANAAN SMALL CELL LUNG CANCER - Sari, Felicia Puspita; Satrio, Kenny; Sastrawan, I Gede Gita (Essential: Essence of Scientific Medical Journal; Vol 16 No 1 (2018): Volume 16 No. 1 (Januari-Juni) : Essence Of Scientific Medical Journal, 2018)
Background: Lung cancer is a type of cancer with the highest incidence in Indonesia. In general, lung cancer can be divided into two groups based on its histopathology, which are Non-Small Cell Lung Cancer (NSCLC) and Small Cell Lung Cancer (SCLC). Small Cell Lung Cancer (SCLC) is originated from neuroendocrine precursor cell and has a very fast and uncontrollable cell growth characteristic. Cigarette consumption is closely related with SCLC because studies show that most of SCLC patients have a history of smoking. Consequently, an increase in the number of smokers in recent years is also accompanied by an increase in the incidence and mortality rates by SCLC. Method : This review was made by using relevant journals from proquest.com, sciencedirect.com and scholar.google.com database with keywords Lung cancer, TRPA1, SCLC. Results: TRPA1 functions as an ion canal that helps the entry of Ca 2+ into the cells. In SCLC patients, TRPA1 is expressed highly in content compared to NSCLC and normal patients. TRPA1 holds an important role in many SCLC cell viability mechanisms. Continuous activation of TRPA1 will mediate the increase of Ca 2+ influx into cancer cell thus causing an increase in SCLC progressivity. In other words, inhibition of TRPA1 will obstruct the process of Ca 2+ influx into the cell which is followed by induction of apoptosis along with inhibition of metastasis, angiogenesis, also progressivity of SCLC. Conclusion: TRPA1 is expressed in a significant numbers in SCLC cell, this ion canal can be used as a promising therapeutic intervention target in the future.